Hip Arthroscopy for Femoroacetabular Impingement: Minimal Clinically Important Difference Rates Decline From 1- to 5-Year Outcomes - Berkcan Akpinar, M.D; Lawrence J. Lin, B.A; David A. Bloom, B.S; Thomas Youm, M.D (Elsevier, 2021)
Purpose: To correlate patient-reported outcomes (PROs) and minimal clinically important difference (MCID) achievement rates after hip arthroscopy for femoroacetabular impingement syndrome (FAI). Methods: Patients with clinically diagnosed FAI who underwent primary hip arthroscopy from September 2012 to March 2014 with a minimum of 5-year outcomes were identified. Patients undergoing labral debridement, microfracture, bilateral procedures, with evidence of dysplasia, Tönnis grade >1, and joint space <2 mm were excluded. Analysis of variance was used to compare PROs. Survival rates were determined using Kaplan-Meier analysis. Regression analysis identified associations with modified Harris Hip Scores (mHHS), minimal clinically important difference (MCID) rates, and Nonarthritic Hip Scores (NAHS). Results: A total of 85 of 101 eligible consecutive patients (84% inclusion) (age: 41.4 ± 14.0 years; 69% female, mean body mass index [BMI] 25.0 ± 4.2) met inclusion and exclusion criteria. Patients underwent labral repair (100%) and a combination of cam (86%) and pincer resection (99%). The 5-year survival-to-revision rate was 77% whereas 5-year survival rate to total hip arthroplasty was 94%. The 1-year (87.4 ± 13.6) and 5-year (84.5 ± 13.5) mHHS scores were greater versus preoperative scores (46.3 ± 11.3, P < .001). There was a decrease in MCID rate between 1-year (n = 74, 87%) and 5-year (n = 61, 73%, P = .019) outcomes. The 1-year (87.4 ± 12.7) and 5-year (89.2 ± 15.8) NAHS scores were greater versus preoperative scores (49.7 ± 12.7, P < .001). Regression demonstrated associations between BMI (MCID: P = .033; NAHS: P = .010), age (mHHS: P = .031), and cam resection (mHHS: P = .010) with 5-year outcomes. Conclusions: There is a decline in MCID at 5-year follow-up after hip arthroscopy for FAI. Lower BMI, younger age, and cam resection are associated with positive outcomes. There is excellent index procedure survivability and excellent total hip arthroplasty prevention rate. Level of Evidence: Level IV.